2013
DOI: 10.1007/s00167-013-2665-y
|View full text |Cite
|
Sign up to set email alerts
|

Utility of multimodal analgesia with fascia iliaca blockade for acute pain management following hip arthroscopy

Abstract: In this prospective study, multimodal analgesia with fascia iliaca blockade following hip arthroscopy was safe and effective. The quality of early post-operative analgesia provided by the fascia iliaca blockade was excellent and resulted in low opioid consumption, high quality of pain relief and high overall patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 23 publications
4
47
1
Order By: Relevance
“…Goitia Arrola et al [20] performed a prospective observational study of 41 patients undergoing total hip replacement surgery, and the FICB was effective in controlling early postoperative pain after surgery. Moreover, Krych et al [21] reported that the FICB decreased the opioid consumption, and provided a high quality of pain relief and high overall patient satisfaction in patients with hip surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Goitia Arrola et al [20] performed a prospective observational study of 41 patients undergoing total hip replacement surgery, and the FICB was effective in controlling early postoperative pain after surgery. Moreover, Krych et al [21] reported that the FICB decreased the opioid consumption, and provided a high quality of pain relief and high overall patient satisfaction in patients with hip surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[18] included 30 patients who received a fascia iliaca block prior to surgery. There was no control group.…”
Section: Resultsmentioning
confidence: 99%
“…In our analysis two studies evaluated the effect on pain scores of a FIB after hip arthroscopy. In the group of Krych et al [18], 30 consecutive patients received a FIB and all patients left the hospital the same day of surgery, with mean Day 0 reported VAS scores 4.7. This study lacked a control group and multimodal analgesia was used, therefore it cannot be said what the sole effect was of the FIB.…”
Section: Discussionmentioning
confidence: 99%
“…For all 6 included studies, [16][17][18][27][28][29] data were collected regarding the study specifics, patients included, and outcomes measured in the study. The journal of publication, type of study, level of evidence, and type of PNB, as well as the presence of a comparator group were noted ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Schroeder and colleagues 17 examined patients receiving general anesthesia and lumbar plexus block and found a significant reduction in pain immediately postoperatively in the PACU, though these effects disappeared the day following the procedure. Krych and colleagues 27 also reported on postoperative pain in patients undergoing fascia iliaca blockade, although they did not include a comparator group. Outcome comparison between patients who received PNB and controls in the PACU and 1 day following the procedure are presented in Table 4.…”
Section: Postoperative Painmentioning
confidence: 99%